Avalanche‐Discharge‐Induced Electrical Forming in Tantalum Oxide‐Based Metal–Insulator–Metal Structures. (30th October 2015) - Skaja, Katharina; Bäumer, Christoph; Peters, Oliver; Menzel, Stephan; Moors, Marco; Du, Hongchu; Bornhöfft, Manuel; Schmitz, Christoph; Feyer, Vitaliy; Jia, Chun‐Lin; Schneider, Claus Michael; Mayer, Joachim; et al.
Abstract : Oxide‐based metal–insulator–metal structures are of special interest for future resistive random‐access memories. In such cells, redox processes on the nanoscale occur during resistive switching, which are initiated by the reversible movement of native donors, such as oxygen vacancies. The formation of these filaments is mainly attributed to an enhanced oxygen diffusion due to Joule heating in an electric field or due to electrical breakdown. Here, the development of a dendrite‐like structure, which is induced by an avalanche discharge between the top electrode and the Ta2 O5‐ x layer, is presented, which occurs instead of a local breakdown between top and bottom electrode. The dendrite‐like structure evolves primarily at structures with a pronounced interface adsorbate layer. Furthermore, local conductive atomic force microscopy reveals that the entire dendrite region becomes conductive. Via spectromicroscopy it is demonstrated that the subsequent switching is caused by a valence change between Ta 4+ and Ta 5+, which takes place over the entire former Pt/Ta2 O5‐ x interface of the dendrite‐like structure. Abstract : It is experimentally demonstrated that a pronounced interface adsorbate layer in Ta2 O5– x ‐based resistive switching devices leads to an avalanche‐discharge‐induced breakdown instead of a breakdown within a single filament. Moreover, it is explicitly proven that the switching between the low and high resistance state is caused by the reduction/oxidation of Ta2 O5– x /TaO2 in the entire former Pt/Ta2 O5– x interface of the dendrite‐like structure.